Pulse electric field assisted process for extraction of Jiuzao glutelin extract and its physicochemical properties and biological activities investigation. (30th July 2022) - Jiang, Yunsong; Xing, Mengzhen; Kang, Qiao; Sun, Jinyuan; Zeng, Xin-an; Gao, Wenhong; Li, Hehe; Gao, Yunhua; Li, Anjun
Graphical abstract: Highlights: The extraction content of Jiuzao glutelin extraction (JGE) was improved by pulsed electric field. Sorghum glutelin (SG) accounted for the 59.16% of JGE. JGE three-dimensional structures were predicted for the first time. JGE showed good foaming ability, foam stability, water and oil holding capacity, and a dense structure. JGE exhibited ABTS, DPPH, hydroxyl radical scavenging, ACE inhibitory activities, and high cell biocompatibility (under 2.5 mg/mL). Abstract: Jiuzao is the residue of baijiu distillation. In this study, pulse electric field (PEF) was used to improve the extraction efficiency of Jiuzao glutelin extract (JGE). The species, physicochemical properties, and biological activities of JGE were investigated to expand its utilization. The results showed that after treatment with PEF under optimal conditions (pulse times, 83 in total; strength, 3.26 kV/cm; Jiuzao/distilled water, 3:20), the JGE content increased by 13.81% compared with ultrasound auxiliary extraction. 59.16% of the JGE was identified to be from sorghum. JGE exhibited desirable foaming, foam stability, water and oil holding capacities, and in vitro antioxidant and angiotensin-converting enzyme inhibitory activities (the IC50 value was 0.61 mg/mL). In addition, JGE exhibited high cell compatibility at proper concentrations in Caco-2 and CCD 841 CON cells. Overall, PEF is a potential technique to extract high-quality JGE from Jiuzao due to its high yield, efficiency, and maintenance of JGE bioactivities.